The CISO Handbook - Gentile, Michael; Collette, Ron; August, Thomas (Auerbach Publications, 2016)
The CISO Handbook: A Practical Guide to Securing Your Company provides unique insights and guidance into designing and implementing an information security program, delivering true value to the stakeholders of a company. The authors present several essential high-level concepts before building a robust framework that will enable you to map the conc.